Inovasi Pengembangan Bahan Ajar Kewirausahaan Berbasis Learning Management System di Politeknik Pelayaran Sumatera Barat - Nazarwin, Nazarwin; Kurniawan, Edi; Kurniawan, M. (Universitas Negeri Padang, 2025)
This study aimed to develop an entrepreneurship teaching module utilizing a Learning Management System (LMS) to enhance the learning process at the Politeknik Pelayaran Sumatera Barat. The module was designed using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. The research involved 72 students from the Marine Transportation program in the odd semester of the 2024/2025 academic year. Material and media experts conducted validation using observation sheets and questionnaires. The findings indicated that the LMS-based module achieved excellent validity, with an average expert validation score of 91.2%.Furthermore, students' responses regarding usability, ease of use, and user satisfaction were categorized as